2014
DOI: 10.5624/isd.2014.44.3.229
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of bifid and trifid mandibular canals using cone-beam computed tomography

Abstract: PurposeTo investigate the prevalence of bifid and trifid mandibular canals using cone-beam computed tomography (CBCT) images, and to measure their length, diameter, and angle.Materials and MethodsCBCT images of 500 patients, involving 755 hemi-mandibles, were used for this study. The presence and type of bifid mandibular canal was evaluated according to a modified classification of Naitoh et al. Prevalence rates were determined according to age group, gender, and type. Further, their diameter, length, and angl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
64
7
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(99 citation statements)
references
References 17 publications
1
64
7
10
Order By: Relevance
“…Recent studies employed CBCT images where Rashsuren et al, [11] Yang et al, [12] and Orhan et al [13] found the prevalence as high as 22.6%, 31.1%, and 46.5%, respectively, compared to the prevalence of 5.63% found in the present study using CBCT images. Sanchis et al [9] reported female predilection; however, in the present study, male predilection was found.…”
Section: Discussioncontrasting
confidence: 43%
“…Recent studies employed CBCT images where Rashsuren et al, [11] Yang et al, [12] and Orhan et al [13] found the prevalence as high as 22.6%, 31.1%, and 46.5%, respectively, compared to the prevalence of 5.63% found in the present study using CBCT images. Sanchis et al [9] reported female predilection; however, in the present study, male predilection was found.…”
Section: Discussioncontrasting
confidence: 43%
“…28 The rest 3,18,21,[29][30][31][32][33][34][35][36][37][38][39] of the studies were published in dental journals. Sample sizes ranged from 308 38 to 1933 32 CT images and from 350 39 to 6000 panoramic radiographic images.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Sample sizes ranged from 308 38 to 1933 32 CT images and from 350 39 to 6000 panoramic radiographic images. 21 The studies were conducted in nine different countries: Brazil, 30,34,36,37 Canada, 28 Chile, 39 India, 33 Korea, 29,31,32,35 South Africa, 3 Spain, 18 Taiwan 38 and USA. 21 Most of the articles were published in English, 3,18,21,28,29,[31][32][33][34][35]38,39 and three articles were published in Portuguese.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Contudo apresentam limitações inerentes à técnica radiográfica, como a não observação da relação vestíbulo-lingual com outras estruturas anatômicas 1,8,9 . A presença de imagens produzidas por reparos anatômicos como a impressão do nervo milo-hioideo na superfície interna da mandíbula, ou ainda uma condensação radiográfica causada pela inserção do musculo milo-hioideo na superfície interna da mandíbula, paralela ao canal mandibular [10][11][12] . Levando em conta a importância do procedimento, se faz necessária tomográfica computadorizada, a qual permite avaliação mais detalhada 13,14 .…”
Section: Discussionunclassified